Proses Layanan Bimbingan Belajar dalam Meningkatkan Kemampuan Belajar Anak di Gunung Sari Ilir - Rahayu Sri Waskitoningtyas; Ganjar Susilo; Besse Intan Permatasari (Jurnal SOLMA, 2022)
Background: Now the awareness of parents to give tutoring or tutoring to their children when outside of school. Various kinds of tutoring service processes can be provided to students in improving their learning outcomes so that they can be optimal. This community service aims to find out how the tutoring process works in improving children's learning abilities in Gunung Sari Ilir. Methods: This PKM is a type of qualitative research with a qualitative descriptive approach. The subjects in this PKM were elementary school children who took tutoring at Gunung Sari Ilir, with purposive sampling as the subject. Results: With students participating in tutoring activities like this, it is expected that students will be able to find ways of learning according to their abilities. The quality of the teaching-learning process is increasing and can improve student learning outcomes. Giving material when the process of tutoring services in class is able to analyze the academic level of students. Based on the PKM that has been done, it can be concluded that students are very attentive when the teacher explains, students are also enthusiastic about answering teacher questions, students are also enthusiastic in answering questions on the blackboard so that the learning ability of each child increases